Otago Glaucoma Surgery Outcome Study: Examining the Development of Strabismus Causing Diplopia in Patients Who Have Received Molteno Implant Surgery. Issue 2 (2nd April 2020) - Borowsky, Thomas; Bevin, Tui H.; Thompson, Andrew M.; Herbison, Peter; Molteno, Anthony C. B.; Mitchell, Logan
ABSTRACT: Objective: To evaluate the development of postoperative strabismus causing diplopia in patients who received Molteno implant surgery for the treatment of glaucoma. Methods: The Otago Glaucoma Surgery Outcome study (OGSOS) was used to select cases who had undergone Molteno implant surgery to examine the effect on the development of strabismus causing diplopia. Information was collected on treatments provided to correct motility disturbance, and their success, in this retrospective non-comparative study. Results: 32 cases (3.3%) were found to have developed diplopia following the Molteno implant surgery from a total of 977 cases. Of these, the strabismus in 23 cases was described in sufficient detail to permit clinical categorization. Most (19/23) demonstrated an exodeviation, hyperdeviation, or a combination thereof, although 2/6 cases with superonasal plate location demonstrated a hypodeviation. Diplopia generally resolved spontaneously (20/32 cases). Treatment was required in eight cases, usually conservative and successful (6/8 cases), but strabismus surgery was required in two cases, and was unsuccessful. Conclusions: This study found a low incidence of diplopia developing post-Molteno implant surgery. Strabismus features suggested a restrictive etiology, and spontaneous recovery was common (62.5%). Surgical correction proved unsuccessful – confirming persistent postoperative diplopia after Molteno implant surgery to be a rare but surgically challenging complication.